2017
DOI: 10.1002/ajp.22657
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive status affects the feeding ecology and social association patterns of female squirrel monkeys (Saimiri collinsi) in an Amazonian rainforest

Abstract: When making foraging decisions, female primates may follow specific behavioral strategies that reflect their reproductive state. Lactation is considered the most energetically costly phase for females, but we argue that gestation is also energetically expensive for squirrel monkeys. In this study, we examined whether female squirrel monkeys (a seasonally breeding primate) in different reproductive phases showed significant differences in their foraging ecology. We sampled two wild groups of squirrel monkeys (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…It has seldom been demonstrated that diet selection in the wild specifically tracks changes in requirements for particular macronutrients. Many studies have shown that mammals increase energy intake during lactation (Cui et al., 2018; Douhard et al., 2016; Droscher et al., 2016; Speakman, 2008), and that they change their diet compositions with a shift to higher protein foods (Dias et al., 2011; Ruivo et al., 2017; Rydell, 1989; Tirado Herrera & Heymann, 2004); few, however, have demonstrated that they specifically select a diet with different macronutrient ratios than when not lactating. Guo et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has seldom been demonstrated that diet selection in the wild specifically tracks changes in requirements for particular macronutrients. Many studies have shown that mammals increase energy intake during lactation (Cui et al., 2018; Douhard et al., 2016; Droscher et al., 2016; Speakman, 2008), and that they change their diet compositions with a shift to higher protein foods (Dias et al., 2011; Ruivo et al., 2017; Rydell, 1989; Tirado Herrera & Heymann, 2004); few, however, have demonstrated that they specifically select a diet with different macronutrient ratios than when not lactating. Guo et al.…”
Section: Discussionmentioning
confidence: 99%
“…It has seldom been demonstrated that diet selection in the wild specifically tracks changes in requirements for particular macronutrients. Many studies have shown that mammals increase energy intake during lactation (Cui et al, 2018;Douhard et al, 2016;Droscher et al, 2016;Speakman, 2008), and that they change their diet compositions with a shift to higher protein foods (Dias et al, 2011;Ruivo et al, 2017;Rydell, 1989;Tirado Herrera & Heymann, 2004); few, however, have demonstrated that they specifically select a diet with different macronutrient ratios than when not lactating. Guo et al (2018) found for a different wild population of R. roxellana than this study that intake of fat and carbohydrate, which in primates are the principle macronutrients used in energy metabolism, increased during the cold winter compared with spring, by an amount that closely matched the seasonal difference in energetic requirements for thermoregulation, whereas protein intake remained unchanged.…”
Section: Diet Selectionmentioning
confidence: 99%
“…In order to support such reproductive demands, female S. collinsi in our population consume more animal protein than do males, year-round, but particularly during gestation. In addition, during lactation, females cope with the extra energetic requirements by altering their foraging behaviors and activity budgets (Ruivo et al, 2017). Therefore, females are able to show behavioral flexibility that likely maximizes maternal survival.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the social activity among levels of pregnancy were not significantly different. Ruivo et al (2017) and Gould et al (2011) stated that due to the high energy and nutritional needs during pregnancy, females in the early gestation period will spend a lot of time eating. This behavior aims to compensate for the nutrition shared with the fetus.…”
Section: Female Behavior During Reproductionmentioning
confidence: 99%